The manager's guide to web application security : a concise guide to the weaker side of the web - Lepofsky, Ron (Apress, 2014)
The Manager's Guide to Web Application Security is a concise, information-packed guide to application security risks every organization faces, written in plain language, with guidance on how to deal with those issues quickly and effectively. Often, security vulnerabilities are difficult to understand and quantify because they are the result of intricate programming deficiencies and highly technical issues. Author and noted industry expert Ron Lepofsky breaks down the technical barrier and identifies many real-world examples of security vulnerabilities commonly found by IT security auditors, translates them into business risks with identifiable consequences, and provides practical guidance about mitigating them. The Manager's Guide to Web Application Security describes how to fix and prevent these vulnerabilities in easy-to-understand discussions of vulnerability classes and their remediation. For easy reference, the information is also presented schematically in Excel spreadsheets available to readers for free download from the publisher's digital annex. The book is current, concise, and to the point-which is to help managers cut through the technical jargon and make the business decisions required to find, fix, and prevent serious vulnerabilities.